MANAJEMEN PENINGKATAN MOTIVASI KERJA TERHADAP ADAPTASI BUDAYA KERJA SELAMA MASA BEKERJA DARI RUMAH (WORK FROM HOME) PADA PERUSAHAAN PT. GEMILANG RIZKY MEDIKA - Sadiqin, Amin (Transpublika Publisher, 2022)
This study aims to determine the causes of employees losing their work motivation, signs of employees experiencing a decrease in work motivation, the obstacles of leaders in increasing employee motivation during WFH, and looking for strategic recommendations that can be given to company leaders in increasing employee motivation at PT. Gemilang Rizky Medika when there was a change in organizational culture. This study uses a qualitative approach. The data was obtained by interviewing the owner of the company. The results of this study indicate that the cause of employees of PT Gemilang Rizky Medika losing work motivation when organizational culture changes occur, among others, being unfamiliar with the work system at home, lack of work facilities at home and lack of coordination between teams. The forms of motivation given by the leadership of PT Gemilang Rizky Medika to employees during WFH include: 1) communication between leaders and subordinates must run well; 2) awarding employees; 3) work flexibility that is not too tight and 4) providing supervision and punishment to employees.